Pemberian ASI Eksklusif dengan Kejadian Diare - Yampa Eksa Daidella Ghilari; Trisno Agung; Isabella Rahmawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
ABSTRACTBackground: Diarrhea is a disease with a high incidence in the world. One risk factor for diarrhea is that the mother does not give exclusive breastfeeding to her baby. The coverage of exclusive breastfeeding in Banguntapan I Health Center Bantul from 302 infants as many as 197 (90%) infants who received exclusive breastfeeding.Objective: To determine the relationship and calculate the risk of exclusive breastfeeding with the incidence of diarrhea in Banguntapan I health center, Bantul.Method: This study is a type of quantitative research using methods analytical survey with crossectional approach. The population is mothers who have babies aged> 6-12 months in Banguntapan I Health Center, Bantul. The sampling technique used purposive sampling, with a total sample of 75 respondents.Results: From 75 samples there were 51 exclusively breastfed babies and 24 infants who were not given exclusive breastfeeding. Babies with exclusive breastfeeding and having diarrhea as many as 3 babies (4.0%), while babies with no breast milk exclusive and experienced diarrhea of 6 babies (8.0%). With the chi-square test obtained p value of 0.026 (p> 0.05). The Prevalence Ratio value (RP) obtained a value of 4,250 (interval 90% trust).Conclusion: There is a relationship between exclusive breastfeeding and the incidence of diarrhea. Mothers who do not give exclusive breastfeeding are 4,250 times more likely to be babies to experience diarrhea compared to mothers who give exclusive breastfeeding, and on a regular basis statistically significant (0.026).Keywords: Exclusive breastfeeding, incidence of diarrhea. INTISARILatar Belakang: Diare merupakan salah satu penyakit dengan insidensi tinggi di dunia. Salah satu faktor risiko diare adalah ibu tidak memberikan ASI eksklusif kepada bayinya. Cakupan pemberian ASI eksklusif di Puskesmas Banguntapan I Bantul dari 302 bayi sebanyak 197 (90%) bayi yang mendapatkan ASI eksklusif.Tujuan: Mengetahui hubungan dan menghitung risiko pemberian ASI eksklusif dengan kejadian diare di puskesmas Banguntapan I Bantul.Metode: Penelitian ini merupakan jenis penelitian kuantitatif menggunakan metode survey analitik dengan pendekatan crossectional. Populasinya adalah ibu yang memiliki bayi umur >6-12 bulan di puskesmas Banguntapan I Bantul. Teknik pengambilan sampel menggunakan purposive sampling, dengan jumlah sampel sebanyak 75 responden.Hasil Penelitian: Dari 75 sampel terdapat 51 bayi yang diberikan ASI eksklusif dan 24 bayi yang tidak diberikan ASI eksklusif. Bayi dengan diberikan ASI eksklusif dan mengalami diare sebanyak 3 bayi (4,0%), sedangkan bayi dengan tidak diberikan ASI eksklusif dan mengalami diare sebanyak 6 bayi (8,0%). Dengan uji chi-square diperoleh nilai p sebesar 0,026 (p>0,05). Nilai Ratio Prevalensi (RP) diperoleh nilai 4,250 (Interval kepercayaan 90%).Kesimpulan: Terdapat hubungan antara pemberian ASI eksklusif dengan kejadian diare. Ibu yang tidak memberikan ASI eksklusif 4,250 kali lebih besar kemungkinan bayinya untuk mengalami diare dibanding dengan ibu yang memberikan ASI eksklusif, dan secara statistik bermakna (0,026).Kata Kunci: Pemberian ASI eksklusif, kejadian diare